Comparison between Tramadol and Meperidine for Treating Shivering in Patients undergoing Surgery under Spinal Anaesthesia - Acharya, Sulav; Dhakal, N (Nepal Medical College Journal, 2020)
Shivering during regional anesthesia is a common problem and is distressing for patients with variety of complications. Therefore this study was conducted to compare the efficacy, potency, hemodynamic effects and side effects of tramadol with that of meperidine for the control of shivering during Spinal Anaesthesia. Sixty patients of ASA physical status I or II, aged 18 to 65 years, undergoing routine surgery under spinal anaesthesia and developed shivering intraoperatively were randomly allocated to receive 0.5 mg/kg meperidine intravenously (Group A, n=30) or 0.5 mg/kg tramadol intravenously (Group B, n=30). Treatment that stopped shivering was considered to have been successful. The response rate was 100 % in both the groups. The time that elapsed from treatment to the time shivering ceased was 5.37±2.20 minutes for meperidine group and 5.87±2.92 minutes for tramadol group (p>0.05). The number of patients who assessed treatment efficacy as no, partial or marked improvement was 0, 2 and 28 for meperidine group and 0, 3 and 27 for tramadol group (p>0.05). Only two patients receiving meperidine developed pruritis and both the grops were similar in terms of Haemodynamic response. The result of this study concluded that tramadol (0.5 mg/kg) is as effective as meperidine (0.5 mg/kg) for treating post anaesthetic shivering with high safety profile.